Bacillus proteolyticus OSUB18 triggers induced systemic resistance against bacterial and fungal pathogens in Arabidopsis - Yang, Piao; Zhao, Zhenzhen; Fan, Jiangbo; Liang, Yinping; Bernier, Matthew C.; Gao, Yu; Zhao, Lijing; Opiyo, Stephen Obol; Xia, Ye (Frontiers in Plant Science, 2023)
Pseudomonas syringae and Botrytis cinerea cause destructive bacterial speck and grey mold diseases in many plant species, leading to substantial economic losses in agricultural production. Our study discovered that the application of Bacillus proteolyticus strain OSUB18 as a root-drench enhanced the resistance of Arabidopsis plants against P. syringae and B. cinerea through activating Induced Systemic Resistance (ISR). The underlying mechanisms by which OSUB18 activates ISR were studied. Our results revealed that the Arabidopsis plants with OSUB18 root-drench showed the enhanced callose deposition and ROS production when inoculated with Pseudomonas syringae and Botrytis cinerea pathogens, respectively. Also, the increased salicylic acid (SA) levels were detected in the OSUB18 root-drenched plants compared with the water root-drenched plants after the P. syringae infection. In contrast, the OSUB18 root-drenched plants produced significantly higher levels of jasmonyl isoleucine (JA-Ile) than the water root-drenched control after the B. cinerea infection. The qRT-PCR analyses indicated that the ISR-responsive gene MYC2 and the ROS-responsive gene RBOHD were significantly upregulated in OSUB18 root-drenched plants upon both pathogen infections compared with the controls. Also, twenty-four hours after the bacterial or fungal inoculation, the OSUB18 root-drenched plants showed the upregulated expression levels of SA-related genes (PR1, PR2, PR5, EDS5, and SID2) or JA-related genes (PDF1.2, LOX3, JAR1 and COI1), respectively, which were consistent with the related hormone levels upon these two different pathogen infections. Moreover, OSUB18 can trigger ISR in jar1 or sid2 mutants but not in myc2 or npr1 mutants, depending on the pathogen's lifestyles. In addition, OSUB18 prompted the production of acetoin, which was reported as a novel rhizobacterial ISR elicitor. In summary, our studies discover that OSUB18 is a novel ISR inducer that primes plants' resistance against bacterial and fungal pathogens by enhancing the callose deposition and ROS accumulation, increasing the production of specific phytohormones and other metabolites involved in plant defense, and elevating the expression levels of multiple defense genes.